Electrodeposition of Ni3Se2/MoSex as a bifunctional electrocatalyst towards highly-efficient overall water splitting. Issue 45 (14th November 2020) - Tian, Yifan; Xue, Xinying; Gu, Yu; Yang, Zhaoxi; Hong, Guo; Wang, Chundong
Abstract : Electrochemically splitting water into hydrogen and oxygen plays a significant role in the commercialization of hydrogen energy as well as fuel cells, but it remains a challenge to design and fabricate low-cost and high-efficiency electrocatalysts. Abstract : Electrochemically splitting water into hydrogen and oxygen plays a significant role in the commercialization of hydrogen energy as well as fuel cells, but it remains a challenge to design and fabricate low-cost and high-efficiency electrocatalysts. Herein, we successfully prepared Ni3 Se2 /MoSe x on nickel foam via a facile electrodeposition method. To understand the electrochemical mechanism occurring in the electrodeposition process, a new model was proposed, providing insight into the nucleation and growth of deposited materials. The as-prepared Ni3 Se2 /MoSe x exhibits splendid electrochemical performance with 82 mV and 270 mV overpotentials to drive a current density of 10 mA cm −2 in 1 M KOH aqueous solution for HER and OER, respectively. Moreover, a driving potential of 1.57 V is required to reach a current density of 10 mA cm −2 for a configured full cell with Ni3 Se2 /MoSe x working as both the anode and cathode towards overall water splitting, outperforming the state-of-the-art commercial full cells assembled with noble-based metals. The advanced catalytic performance should be attributed to the numerous in situ formed interfaces, allowing π-electron transfer from Ni to Mo via O 2− bridging, subsequently optimizing the adsorption features of oxygenated species (OER) and favorable Volmer/Heyrovsky reaction (HER). This work offers an effective and scalable fabrication prototype for the preparation of bifunctional electrocatalysts with electrodeposition.